Pendampingan Desain Perencanaan dan RAB Masjid Desa Denanyar Kecamatan Tangen Kabupaten Sragen - Asri Nurdiana; Sutanto Sutanto; Lukman Lukman (Sekolah Vokasi Universitas Diponegoro, 2023)
In infrastructure planning in the village, the village government follows the Law of the Republic of Indonesia Number 6 of 2014 concerning Villages and Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 113 of 2014 concerning Village Financial Management. The problem that then arises is that, in several villages, the quality of existing human resources does not support the planning of village facilities and infrastructure independently. In this community service activity, the Team will collaborate with Denanyar Village officials, Tangen District, Sragen Regency to assist in planning public facilities such as mosques. It is hoped that planning a mosque in Denanyar Village will assist the village government in preparing infrastructure that accommodates the needs of the community, especially in worship.